2013
DOI: 10.1109/tvcg.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Evaluation of Virtual Walking Trajectories

Abstract: Fig. 1. The objective of this paper is to evaluate various virtual locomotion conditions by comparing reference with virtual trajectories formed during goal-directed locomotion tasks. Reference trajectories (left) can be recorded through motion capture or be generated through a numerical model of human locomotion. The paper demonstrates the framework (center) over a set of experimental trajectories (right). For the purpose of demonstration, this paper compares frequently used virtual locomotion conditions. Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…Figure 21 shows the visibility and resulting estimated paths for the example C3. The model used here is the one by Cirio et al [3]. It can be seen that the paths indeed lead to reasonable target locations and they can be used to plan redirection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 21 shows the visibility and resulting estimated paths for the example C3. The model used here is the one by Cirio et al [3]. It can be seen that the paths indeed lead to reasonable target locations and they can be used to plan redirection.…”
Section: Discussionmentioning
confidence: 95%
“…The user position was Figure 21: Mesh C3 with visibility (red) and estimated locomotion paths for four waypoint targets. The possible user paths that were generated using Cirio et al's path model [3].…”
Section: Run-timesmentioning
confidence: 99%
“…Cirio et al [4] observed that the angle α between the target's orientation and the line connecting the target and the user decreases linearly with a user's distance to a target I . Moreover, they observed that a users walking velocity is inversely proportional to his turning speed.…”
Section: Cirio Et Almentioning
confidence: 99%
“…The model by Cirio et al [16] is based on their observation that the distance from user to the target I decreases linearly with the angle α between the target's orientation and the line connecting the target and the user, and the velocity is inversely proportional to the turning speed. Thus, they propose equation (1).…”
Section: ) Cirio Et Almentioning
confidence: 99%